2010
DOI: 10.12968/bjon.2010.19.21.80000
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors leading to depression in the British Army

Abstract: Few studies have explored the predisposing factors leading to depression within the British Army, and this qualitative investigation provides a novel approach to advance knowledge in this poorly researched area. Information was provided by army mental health (MH) clinicians, with results aligned to theoretical groupings under the headings of: occupational stressors; macho culture, stigma and bullying; unhappy young soldier; relationships and gender. These issues were influenced by peacetime and operational set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…In keeping with the concept of knowledge transfer, these factors indicate the increasing potential to translate knowledge gained from nursing research to other health professions. Examples include helicopter evacuation services patient outcome and projects based in mental health (Brewer and Ryan-Wenger, 2009;Ebbs and Timmons, 2008;Finnegan and Finnegan, 2007;Finnegan et al, 2013;Gibbons et al, 2011;Kee et al, 2005;Lairet et al, 2013). This shift also acknowledges the collaborative nature of military healthcare and as a marker of bibliometric profile it signals that the field of military nursing is open to transfer to other disciplines (Estabrooks et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the concept of knowledge transfer, these factors indicate the increasing potential to translate knowledge gained from nursing research to other health professions. Examples include helicopter evacuation services patient outcome and projects based in mental health (Brewer and Ryan-Wenger, 2009;Ebbs and Timmons, 2008;Finnegan and Finnegan, 2007;Finnegan et al, 2013;Gibbons et al, 2011;Kee et al, 2005;Lairet et al, 2013). This shift also acknowledges the collaborative nature of military healthcare and as a marker of bibliometric profile it signals that the field of military nursing is open to transfer to other disciplines (Estabrooks et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although no study has been performed on the indirect role of job variables in depressioninduced self-harming behaviour, the study by Finnegan et al [27] indicated that various factors (such as job factors) led to an increase in depression among members of the British Army. Since other studies revealed that depression leads to an increase in the tendency for self-harming behaviour and suicide [7,10,22,36,37,39,43], it can be concluded that depression has a mediating role in the development of tendency for suicide among militants, which is partly caused by job-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Job-related factors may directly influence such behaviour, and may also indirectly increase the tendency to self-harm behaviour by worsening depression. Some studies suggest that job-related factors contribute to depression, for instance Finnegan et al [27] showed that job problems are antecedents of depression among UK army personnel. Pflanz & Ogle [26] and Hagan & Kay [28] indicated that job-related factors (such as job satisfaction) are associated with depression among military personnel.…”
mentioning
confidence: 99%
“…Similarly, in a study examining men's accounts of masculinity and its relationship to help-seeking behaviour, O'Brien et al reveal that men are less likely to attend to serious health and body symptoms and more likely to believe that it is necessary to endure high degrees of pain and conceal mental health issues (O'Brien et al, 2005). Men's reluctance to discuss mental health issues has been reported across male-dominated occupations such as farming (Harrell, 1986;Fraser et al, 2005;Alston and Kent, 2008), the military (Finnegan et al, 2010), protective services (Cheek and Miller, 1983) and mining (Campbell, 1997).…”
Section: Introductionmentioning
confidence: 99%